COLLABORATIVE GOVERNANCE IN THE IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY (CSR) BY PT PERTAMINA HULU ROKAN IN RIAU PROVINCE - Bahri, Usman; Zuhdi, Sulaiman; Saputra, Trio (Department of Government, FISIP, Universitas Padjadjaran, 2026)
This study examines collaborative governance in the implementation of PT Pertamina Hulu Rokan’s (PHR) Corporate Social Responsibility (CSR) program in Riau Province. The study seeks to investigate the extent to which the dimensions of principled engagement, shared motivation, and capacity for joint action are applied in the implementation of CSR. The study adopts a qualitative approach through the case study strategy. The data was collected through in-depth interviews, focus group discussions (FGDs), and analysis of policy documents. The results show that the implementation of PHR’s CSR through collaborative governance is not yet optimal. Stakeholder engagement remains top-down and has not been supported by deliberative and participatory dialogue mechanisms. The dominance of corporations, low levels of trust, and limited transparency in the decision-making process also continue to weaken actors’ motivation. Also, the capacity for joint action has not developed well due to weak coordination structures, limited collaborative mechanisms, and the absence of a common information system to support the monitoring and evaluation of CSR programs. The findings of this study indicate that the implementation of PHR's CSR remains partial and administrative and is not fully integrated with community needs or the regional development agenda.